1998
DOI: 10.1109/69.687981
|View full text |Cite
|
Sign up to set email alerts
|

Dependability and performance measures for the database practitioner

Abstract: --We estimate the availability, reliability, and mean transaction time (response time) for repairable database configurations, centralized or distributed, in which each service component is continuously available for repair. Reliability, the probability that the entire transaction can execute properly without failure, is computed as a function of mean time to failure (MTTF) and mean time to repair (MTTR). Mean transaction time in the system is a function of the mean service delay time for the transaction over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Finally, the reliability of transaction in the on‐demand computing system considering the conditional steady‐state user‐perceived availability of resources, is computed as Rk,kb,DMi,Aλfalse(Xfalse)=[]k=1nRkfalse(Xfalse).Aλ.[]k=1n1b>kRkbfalse(Xfalse).[]i=1mRDMifalse(Xfalse) where A λ is the steady‐state availability of the resources under the load λ . We take its formula from Mainkar, which is expressed as Aλ=c=1nAc,λQc where ∀ c =1,…, n and A c , λ of available servers, which has been computed as i=0KriΠi with the steady‐state probabilities for the model, which are given as Πi=false(cρfalse)ii!Π0,1ic1 Πi=ccρic!Π0,ic In the above formulation, ρ=λcμ and Q c have been expressed as Qc=n!c!false(ncfalse)!…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the reliability of transaction in the on‐demand computing system considering the conditional steady‐state user‐perceived availability of resources, is computed as Rk,kb,DMi,Aλfalse(Xfalse)=[]k=1nRkfalse(Xfalse).Aλ.[]k=1n1b>kRkbfalse(Xfalse).[]i=1mRDMifalse(Xfalse) where A λ is the steady‐state availability of the resources under the load λ . We take its formula from Mainkar, which is expressed as Aλ=c=1nAc,λQc where ∀ c =1,…, n and A c , λ of available servers, which has been computed as i=0KriΠi with the steady‐state probabilities for the model, which are given as Πi=false(cρfalse)ii!Π0,1ic1 Πi=ccρic!Π0,ic In the above formulation, ρ=λcμ and Q c have been expressed as Qc=n!c!false(ncfalse)!…”
Section: Problem Formulationmentioning
confidence: 99%
“…Finally, the reliability of transaction in the on-demand computing system considering the conditional steady-state user-perceived availability of resources 40 , is computed as…”
Section: Reliability Modelmentioning
confidence: 99%
“…The parameters inserted in the CTMC models (Figures and ) are as follows: failure parameters λ _ O , λ _ B , and λ _ J have equal values and were obtained from Dantas et al ; as the repair parameters μ _ O , μ _ B , and μ _ J found in Dantas et al , these values were chosen because they are values that correspond to fault and repair of systems similar to the one assessed in this paper. Parameters μ _ D and λ _ D were adopted from Teorey and Ng, who perform a dependability and performance analysis in centralized or distributed database. Failover f μ _ J repair rate was defined as an approximate value for automatic recovery, and F parameter, the probability of successful failover, was taken from Bauer et al that uses this value to probability of success of an automatic recovery process.…”
Section: Experimental Studymentioning
confidence: 99%